2004
DOI: 10.1182/blood-2004-01-0229
|View full text |Cite
|
Sign up to set email alerts
|

Renal venous thrombosis in neonates: prothrombotic risk factors and long-term follow-up

Abstract: The present study was designed to evaluate prothrombotic risk profiles in 59 consecutively recruited white neonates with renal venous thrombosis (RVT). The rates of prothrombotic risk factors (PRs)-for example, the factor V (FV) 1691G>A mutation, the factor II ( Of the 59 neonates investigated, 53 revealed renal atrophy, and 13 children additionally suffered from severe arterial hypertension. In conclusion, the present study demonstrates the significance of genetic PR-especially the FV mutation and elevated Lp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
69
1
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(75 citation statements)
references
References 31 publications
2
69
1
3
Order By: Relevance
“…1 The abdomen USG show the complex cystic lesion (5.7 9 3.7 mm) within left adrenal gland homozygous methylenetetrahydrofolate reductase (MTHFR) C677 T polymorphism [4][5][6][7][8][9][10]. Table 1 describes studies in the literature (between 2000 and 2013) that had reported cases of neonatal RVT with prothrombotic risk factors The presence of factor V Leiden mutation markedly increases the risk for renal vein thrombosis, particularly in neonates.…”
Section: Discussionmentioning
confidence: 99%
“…1 The abdomen USG show the complex cystic lesion (5.7 9 3.7 mm) within left adrenal gland homozygous methylenetetrahydrofolate reductase (MTHFR) C677 T polymorphism [4][5][6][7][8][9][10]. Table 1 describes studies in the literature (between 2000 and 2013) that had reported cases of neonatal RVT with prothrombotic risk factors The presence of factor V Leiden mutation markedly increases the risk for renal vein thrombosis, particularly in neonates.…”
Section: Discussionmentioning
confidence: 99%
“…In three of these patients recurrence was during puberty, a time when there is a second, though less pronounced peak of thrombosis that is also associated with a reduction in thrombolytic activity (Siegbahn & Ruusuvaara, 1988). Two of the 4 children with recurrent thrombosis in the study reported by Kosch et al (2004) were from a sub-group of 12 with more than one TP. In an earlier study the same group had followed up 301 The aetiological role of TP in neonatal thrombosis remains uncertain.…”
Section: Thrombophilic Disorders and Neonatal Thrombosismentioning
confidence: 95%
“…One study reported on the recurrence rate of thrombosis during the follow-up of 59 newborns with RVT (Kosch et al, 2004); at presentation 40/59 (67Á8%) had at least one TP compared to only 14/118 (11Á9%) of controls. In a limited follow-up with a median of 4 years, 4/59 (6Á8%) had a second thrombosis; all four of these had one or more TP.…”
Section: Thrombophilic Disorders and Neonatal Thrombosismentioning
confidence: 99%
“…RVT is the commonest non catheter related thrombosis in infancy and neonates 3 . In neonates it is often spontaneous, secondary causes being asphyxia, hypotension, polycythaemia, dehydration, sepsis, maternal SLE, gestational diabetes, homocystinuria, central lines, umbilical vessel catheterization, cyanotic congenital heart disease, angiography, congenital deficiencies of anticoagulants -protein C, S, Antithrombin III, factor V Leiden mutation and prothrombin mutation 4,5 . Haemoconcentration with hypotension leads to sludging in the intrarenal vessels, initiation of thrombus formation and extending to the large vessels 6 .…”
Section: Discussionmentioning
confidence: 99%